ISSUES IN THE RELATIONSHIPS AMONG BALINESE POP MUSIC, TOURISTS, AND THE TOURISM INDUSTRY - Ni Wayan Ardini; Ni Nyoman Sri Astuti; I Komang Darmayuda; Ni Luh Eka Armoni; Ketut Sumerjana (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
Province of Bali, Indonesia, is growing very rapidly as a tourist destination in recent decades. Currently five to six million foreign tourists visit it every year. On the other hand, Balinese pop music has also grown quite intense in the local communities, especially since the 1990s. Nevertheless, so far, there has not been a significant relationship between Balinese pop music, tourists, and the tourism businesses in this province. Balinese pop music has not been a special product of Bali tourism. This research was conducted to explore and criticize a number of factors that led to the lack of acceptance of the music as part of tourism industry. This literature study was conducted with a descriptive-qualitative approach. The results of the study show that the similarity of Balinese pop music genres to modern music in general is one of the factors. Taste of the tourists, the destinations chosen, lack of promotion, theme of the songs/music, composition, and language used in the lyrics cause the fact that Balinese pop music is less accepted by tourists, especially foreign tourists. It takes certain efforts from artists (musicians), music industry and tourism industries, and also governments to make certain concerted efforts if Balinese pop music wants to be accepted in a tourism business parallel to traditional music products which are already consumed by tourists.